The Performance Implications of Management Control Systems and Dynamic Capabilities: Evidence from Vietnam - Huyen Mong Le; Trang Cam Hoang (Asian Academy of Management Journal, 2024)
Drawing on the resource-based view and dynamic-capability view, this study examines the relationship between the interactive use of management control systems, dynamic capabilities, and firm performance in the Vietnamese information and communication technology industry. The research model and hypotheses have been tested by partial least squares-structural equation modelling (PLS-SEM) with 240 survey samples obtained from managers working in Vietnamese information and communication technology firms. The results indicate that the interactive use of management control systems has a positive effect on dynamic capabilities. Additionally, both the interactive use of management control systems and dynamic capabilities have direct positive effects on firm performance. The results reveal that dynamic capabilities complementary mediate the relationships between the interactive use of management control systems and firm performance. This study provides theoretical and managerial implications for Vietnamese information and communication technology firms that are striving to develop management control systems and dynamic capabilities for enhancing firm performance.